Strategi Penguatan Identitas Kopi Desa Ciater Kabupaten Subang - Arif Purbantara; Emma Rahmawati; Varenna Faubiany; Taufan Daniarta Sukarno (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2022)
The level of coffee consumption in Indonesia has developed very rapidly in the last decade. The many variants of coffee that are widely circulated in the market have led to increased consumer interest from various circles in coffee products. However, ironically, coffee farmers often do not feel the positive impact of the high trend of coffee consumption because their harvests are forced to be fused with other coffee products produced in factories. This is because the coffee does not have a strong identity, so it does not have a high bargaining position and value in the eyes of both producers and consumers. The purpose of this study was to analyze the strategy of strengthening the identity of the village coffee. Data collection was carried out in May – December 2019 through interviews, FGDs, observations and documentation. This research approach uses qualitative methods. This study uses a SWOT analysis by analyzing coffee commodities' internal and external factors. The results show that the strategies that can be used to establish coffee identity are strengthening farmers' social capital, utilizing information technology, training and mentoring farmers in business development, and coordinating between farmer groups and stakeholders in the supply chain.